The effect of the visual awareness education programme on the visual literacy of children aged 5-6*. Issue 3 (27th May 2018) - Özkubat, S.; Ulutaş, İ.
Abstract: The aim of the present study was to investigate the effect of the "Visual Awareness Education Programme" developed to support the visual literacy skills of preschool children. The study group comprised 40 children (20 children in the experimental group and 20 children in the control group) attending preschool in the 2014–2015 school year. The pre-test post-test experimental model was used in the study. The "Visual Literacy Inventory for Preschool Children" and the "Children's Visual Literacy Rating Inventory for Parents" were used to determine visual literacy level of children. Study results revealed significant differences in favour of the experimental group children in the sub-dimensions and the post-test scores of the "Visual Literacy Inventory for Preschool Children" and the post-test scores of the "Children's Visual Literacy Rating Inventory for Parents".